2020
DOI: 10.37880/cumuiibf.671591
|View full text |Cite
|
Sign up to set email alerts
|

Yeni̇lenebi̇li̇r Enerji̇ Tüketi̇mi̇ Ve Ekonomi̇k Büyüme İli̇şki̇si̇: Türki̇ye İçi̇n Bi̇r Toda-Yamamoto Nedenselli̇k Anali̇zi̇

Abstract: Bu çalışma, Türkiye'de 1980Türkiye'de -2018 dönemi için yenilenebilir enerji tüketiminin ekonomik büyüme üzerindeki etkisini incelemektedir. Bunun için çalışmada değişkenlere ilk olarak birim kök testi uygulanmış ve düzey değerlerinin birim kök içerdiği tespit edilmiştir. Birim kök testi sonrasında değişkenler arasında eşbütünleşme ilişkisi sınır ARDL testi ile incelenmiştir. Sınır ARDL testi sonuçlarına göre değişkenler arasında eşbütünleşme ilişkisi bulunmuştur. Test sonucuna göre uzun dönemde yenilenebilir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…According to this view, supportive energy policies will contribute to economic growth. Aslan (2021), Demirgil andBirol (2020), Turkmen et al (2018), Çınar andOz (2017), Cağıl andTürkmen (2013), Saatçi and Dumrul (2013), Mucuk and Uysal (2010) reached conclusions in their analysis for Türkiye that an increase in EC increases EG. In a sectoral study for Türkiye, Koç (2020) concluded that the use of energy used in the transportation, industry and services sectors has a positive effect on growth, while the energy used in the agricultural sector does not affect economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%
“…According to this view, supportive energy policies will contribute to economic growth. Aslan (2021), Demirgil andBirol (2020), Turkmen et al (2018), Çınar andOz (2017), Cağıl andTürkmen (2013), Saatçi and Dumrul (2013), Mucuk and Uysal (2010) reached conclusions in their analysis for Türkiye that an increase in EC increases EG. In a sectoral study for Türkiye, Koç (2020) concluded that the use of energy used in the transportation, industry and services sectors has a positive effect on growth, while the energy used in the agricultural sector does not affect economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%